HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA-TANGAN DENGAN HASIL SHOOTING PADA CABANG OLAHRAGA BOLA BASKET PADA SISWA KELAS X SMA NEGERI 19 PALEMBANG - Lestari, Hikmah (STKIP Pasundan, 2019)
This study aims to determine whether or not there is a relationship between leg muscle power and eye-hand coordination with the results of shooting on basketball in the X grade students of SMA 19 Palembang. The method in this study is correlational. The results of the study stated: (1) there was a significant relationship between leg muscle power and shooting results in basketball; (2) there is a significant correlation between eye-hand coordination and shooting results in basketball; and (3) there is a significant joint relationship between leg muscle power and eye-hand coordination with shooting results in basketball. The conclusion is that there is a relationship between the results of leg muscle power and eye-hand coordination with the results of shooting in basketball in class X SMA Negeri 19 Palembang.